KOMPETENSI KEPALA DESA DALAM PENYELENGGARAAN PEMERINTAHAN DI DESA TOUNELET KECAMATAN KAKAS KABUPATEN MINAHASA - KUENGO, SYAHRUL; Posumah, Johnny Hanny; Dengo, Salmin (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract: The implementation of village governance requires more optimal handling on the aspect of Rural Apparatus Human Resources, in improving the competence of village head and village apparatus. In terms of management, it is necessary to increase the capacity of village government in village development planning and budgeting, village financial management, village head leadership, village policy formulation, and village services. Based on the problems presented, this study aims to determine the competence of the Village Head in the administration in the Village Tounelet Kakas District Minahasa District This research uses qualitative method, which is a contextual research that makes man as an instrument, and adapted to a reasonable situation in relation to data collection which is generally qualitative. The result of the research shows that the competence of Tounelet Village Head in the administration of village government is seen from the competence of knowledge and attitude competence is good enough / adequate; But seen from the competence of skills and skills are still inadequate. Keywords: Village Head Competency, Government Implementation